Students' Creative Thinking Skills in the Implementation of Problem Based Learning (PBL) integrated Brainstrorming Method - Nur Amila Fatmawati; Fitria Eka Wulandari (Universitas Muhammadiyah Sidoarjo, 2020)
This research aims to examine the effect of problem-based learning (PBL) integrated brainstorming learning method on students' creative thinking skill. The method used in this research is Quasi-Experimental with - test and Post- test Control Group design. The sampling in this research is sampling namely 23 students in IX A and 23 in IX D. The instrument applied in this study is a creative thinking test that is made in accordance with the indicators of creative thinking based on . To data, the researcher uses independent sample T-test. The research result showed that there is a significant difference of problem based learning (PBL) integrated brainstorming learning method for students' creative thinking skill.